Insights Obtained by Culturing Saccharibacteria With Their Bacterial Hosts. (June 2020) - Bor, B.; Collins, A.J.; Murugkar, P.P.; Balasubramanian, S.; To, T.T.; Hendrickson, E.L.; Bedree, J.K.; Bidlack, F.B.; Johnston, C.D.; Shi, W.; McLean, J.S.; He, X.; et al.
Oral microbiome research has moved from asking "Who's there?" to "What are they doing?" Understanding what microbes "do" involves multiple approaches, including obtaining genomic information and examining the interspecies interactions. Recently we isolated a human oral Saccharibacteria (TM7) bacterium, HMT-952, strain TM7x, which is an ultrasmall parasite of the oral bacterium Actinomyces odontolyticus. The host-parasite interactions, such as phage-bacterium or Saccharibacteria–host bacterium, are understudied areas with large potential for insight. The Saccharibacteria phylum is a member of Candidate Phyla Radiation, a large lineage previously devoid of cultivated members. However, expanding our understanding of Saccharibacteria-host interactions requires examining multiple phylogenetically distinct Saccharibacteria-host pairs. Here we report the isolation of 3 additional Saccharibacteria species from the human oral cavity in binary coculture with their bacterial hosts. They were obtained by filtering ultrasmall Saccharibacteria cells free of other larger bacteria and inoculating them into cultures of potential host bacteria. The binary cocultures obtained could be stably passaged and studied. Complete closed genomes were obtained and allowed full genome analyses. All have small genomes (<1 Mb) characteristic of parasitic species and dramatically limited de novo synthetic pathway capabilities but include either restriction modification or CRISPR-Cas systems as part of an innate defense against foreign DNA. High levels of gene synteny exist among Saccharibacteria species. Having isolates growing in coculture with their hosts allowed time course studies of growth and parasite-host interactions by phase contrast, fluorescence in situ hybridization, and scanning electron microscopy. The cells of the 4 oral Saccharibacteria species are ultrasmall and could be seen attached to their larger Actinobacteria hosts. Parasite attachment appears to lead to host cell death and lysis. The successful cultivation of Saccharibacteria species has significantly expanded our understanding of these ultrasmall Candidate Phyla Radiation bacteria.